The Effect of Ambient Conditions on the Potential Screening at Ionic Liquid – Electrode Interfaces - Greco, Francesco; Hemmeter, Daniel; Shin, Sunghwan; Steinrück, Hans-Peter; Maier, Florian (Journal of Ionic Liquids, 2022)
In comparison to the clean conditions of ultrahigh vacuum (UHV), we investigate the influence of ambient conditions on the potential screening (PS) at the interfaces of Au and Pt electrodes with the ionic liquids [C8C1Im][Tf2N] and [C8C1Im]Cl. Our study is based on a proof-of-principle experiment that shows that PS measurements performed by XPS yield the same results as measurements using a specific 3-electrode sample holder setup, both in UHV. Based on this, we compare PS measurements under ultraclean conditions by XPS with PS measurements with a 3-electrode setup in N2 and in air. We demonstrate that there is indeed an influence of the ambient gas atmosphere, which depends on applied voltage and combination of IL and electrode material. For Pt electrodes, there is a pronounced influence of the ambient conditions on the PS for both [C8C1Im][Tf2N] and [C8C1Im]Cl, while for Au electrodes hardly any influence is seen. We attribute the observed effects mainly to water affecting the electrical double layers at the IL/electrode interfaces. In addition, we observe that reaction products formed under faradaic conditions can lead to a contamination of the 3rd electrode (reference electrode), yielding time-dependent deviations from the true behavior.
CRIS-Team Scopus Importer:2024-12-16